(3cJGH aj GdHSedIs - (3eMeO GdNGOejs
(3ChdgG (B:s
(3HSe Gddg GdPj LYd GdHSedI TQjYI GdGaJJGM hHYO gPg NRGFf GdLhGgQ heNGRf GdRhGgQ HGH GdHSedI bGd aj GdbGehSs
(3BNQgG (B:s
(3hHGdQMje JeJ GdHSedI hHJeGegG Je GdYGde dchf HMGQ YLGFHgG dG jfbVj CHOG cja dG hgj eaJGM ddcdGe GdbOje hGdMeO ddg QH GdYGdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs